Etos Kerja Para Petani Desa Bakeong Kecamatan Guluk-Guluk Kabupaten Sumenep Dalam Perspektif Ekonomi Islam - Amir Amir (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2023)
Work Ethics in Bakeong Village Farmers who have a high work ethic, and related to the description of the Farmers' Work Ethic, the factors that influence the Farmers' Work Ethics, which are related to the Farmers' Work Ethics in the Islamic Economic Perspective. Bakeong Village Farmers' Work Ethics, factors influencing the Bakeong Village Farmers' Work Ethics, and also to find out the Village Farmers' Work Ethics in the perspective of Islamic Economics. Several important objects in this segment are the Bakeong Village Farmers community. So that the field research method uses a qualitative approach, while the method of extracting data is by using observation, interviews, and documentation. The work ethic of the Bakeong Village Farmers, Guluk-Guluk District, Sumenep Regency can be said to be in accordance with the existing theory, and the work ethic can be said to be high, because it can be seen from several indicators of the work ethic of each Bakeong Village Farmer. Likewise, the work ethic of Bakeong village farmers, Guluk-guluk sub-district, Sumenep district, in the perspective of Islamic Economics is also in accordance with what already exists and is applied in Islam